Impact of Technological Tools on Mathematics Learning - Narváez-Pinango, Miguel; Pozo-Revelo, Diego; Álvarez-Tinajero, Nevy (Revista Ecos de la Academia, 2024)
The use of ICT has been shown to have a positive impact on students’ learning experiences, providing access to diverse sources of knowledge, facilitating interaction with mathematical concepts and promoting participation in the learning process. The objective of this study is to determine the relationship between the use of information and communication technologies (ICT) by high school students in the mathematics learning process. The research is non-experimental, descriptive and correlational; A Cronbach’s Alpha of 0.8 was obtained in the instrument, which was applied to 1822 high school students from the Ibarra canton; For statistical analysis, the Mann-Whitney U test and the Kruskal-Wallis H test were applied. Significant correlations with 95% reliability were found between the use of ICT by students for learning mathematics. The significant relationships between the use of ICT for mathematics learning and gender, ethnic self-identification and liking for mathematics highlight the need for inclusive and specific approaches to the integration of ICT in mathematics education.